PENGARUH CAPITAL STRUCTURE DAN WORKING CAPITAL MANAGEMENT TERHADAP PROFITABILITAS - Dintha IZFS, Ratu; Surachim, Ahim (Journal of Business Management Education (JBME), 2016)
This research was intended to know the impact of capital structure and working capital management on the profitability of PT. Indosat Tbk in the period of 2005-2014. This research applied descriptive and verification method concluded in time series design. The statistic analysis that was used in this study was doubled linear regression at 5% significance level. Based on the findings, it was provable that regression statistic model could applied in noticing the effect of capital structure and working capital structure on profitability through F-test. Moreover, T-test showed that capital structure negatively affected the profitability in significant manner. Lastly, working capital management was identified to be a factor that did not affect the profitability. Keyword : Capital Structure, Debt to Equity Ratio (DER), Working Capital Management, Working Capital Turnover (WCT), Profitability, Return on Equity (ROE).